A review of the black species of Cyclocephala Dejean (Coleoptera: Scarabaeidae: Dynastinae) from Colombia - Neita-Moreno, Jhon C. (Zootaxa, 2021)
The black species of the genus Cyclocephala Dejean (Coleoptera: Scarabaeidae: Dynastinae: Cyclocephalini) from Colombia are reviewed. I define species groups based on the morphology of adults, re-describe those species occurring in Colombia, describe two new species (Cyclocephala santandereana new species and Cyclocephala arhuacana new species), list the species reported for Colombia, provide a key to identify groups and the species within each group, and present species distribution and life history data. This review includes the Cyclocephala cribrata species group previously defined with C. boucheri Dechambre, C. carbonaria Arrow, C. cribrata Burmeister, C. dechambrei Dupuis, C. boliviana Dechambre, C. dilatata (Prell), C. ergastuli Dechambre, C. latipennis Arrow, C. marqueti Dechambre, C. proxima Dechambre, C. rogerpauli Moore, Branham, & Cave, and C. variolosa Burmeister. The Cyclocephala fasciolata species group contains C. abrelata Ratcliffe & Cave, C. brevipennis Endrödi, C. fasciolata Bates, C. melane Bates, and Cyclocephala santandereana new species. The Cyclocephala ligyrina species group has C. arhuacana new species, C. dalensi Ponchel, C. dyscinetoides Dechambre, C. endroedyyoungai Endrödi, C. kaszabi Endrödi, C. ligyrina Bates, Cyclocephala nigerrima Bates, C. rufa Endrödi, and C. scarabaeina (Gyllenhal). Cyclocephala carinatipennis Martínez & Morón is proposed as a new junior synonym of C. rufa Endrödi. A larva of the Cyclocephala cribrata species group is described for the first time. An analysis of the characters of the adults and the described larva of the species group is performed to imply phylogenetic implications. New country records of C. dalensi and C. marqueti are recorded for Colombia.